Disasters are not cute: Cute expressions increase dehumanisation. Issue 5 (3rd September 2021) - Shi, Jiaxin; Qiu, Junjie; Liu, Tuo
Abstract : People perceive cute expressions about situations or events positively or negatively. However, the conditions for how cute expression messaging would be received are less clear. In three studies, we investigated the influences of natural disaster cute expression messaging on audiences to determine the feelings the messaging engendered and perceptions of the content creator's humanity. Study 1 examined cute expression messaging effects of a natural flood disaster. Studies 2 and 3 examined cute expression messaging of the Coronavirus Disease 2019. Study 1 showed that audiences perceived someone using cute expressions to describe a natural disaster as having a lack of humanity. Studies 2 and 3 indicated that cute expressions about the pandemic caused audiences to feel disgusted, leading to a dehumanising perception towards the content creator. Moreover, Study 3 showed that dehumanising the author could further contribute to aggression. From these findings, we conclude that cute expression messaging to describe disasters could be aversive, disrupting perceptions of a shared sense of humanity, and risking aggression against the content creators.